Gefitinib induced severe hyponatremia: A case report. (April 2021) - Meena, Durga Shankar; Kumar, Deepak; Bohra, Gopal Krishana; Midha, Naresh
Introduction: Evolution of targeted molecular therapies has greatly improved patient survival in cancer. Gefitinib is an oral, reversible, epidermal growth factor receptor inhibitor used in advance non-small cell lung cancer. Skin rashes and diarrhea are common adverse effects associated with gefitinib. However, electrolytes disorders are rarely reported with gefitinib, particularly hyponatremia. Case report: We describe a 65-year-old male with metastatic non-small cell lung cancer treated with gefitinib for the last three weeks. He presented to our hospital with complaints of acute onset drowsiness. On evaluation of drowsiness, patient was diagnosed with severe hyponatremia. Management and outcome: After ruling out other common causes of hyponatremia, gefitinib was attributed as a cause of hyponatremia. Gefitinib was immediately stopped and IV hypertonic saline (3% sodium chloride) was started due to severe symptomatic hyponatremia. After seven days of cessation of gefitinib, he became asymptomatic with normalisation of serum sodium levels. Discussion: Hyponatremia in cancer patients is associated with poor prognosis and prolonged hospital stay. Possibility of gefitinib-induced hyponatremia should be considered in order to achieve early diagnosis and prevent significant mortality in cancer patients.